1990
DOI: 10.1007/bf01643432
|View full text |Cite
|
Sign up to set email alerts
|

Single dose fosfomycin trometamol versus multiple dose norfloxacin over three days for uncomplicated UTI in general practice

Abstract: The aim of this study was to carry out a small-scale bacteriological comparison between a standard therapy with norfloxacin 400 mg twice daily, and fosfomycin trometamol (3 g) in single dose in uncomplicated urinary tract infections (UTI) in women. Only patients with UTI with cultures showing a bacterial count of 10(5) or more bacteria/ml were included in the study (n = 32; ages 16-75 years). After one week sterile cultures were obtained in 14 of 16 cases in the fosfomycin trometamol group, and in 14 of 16 cas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

1992
1992
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(5 citation statements)
references
References 6 publications
0
4
0
1
Order By: Relevance
“…Nearly 80% of the studies had low attrition and reporting bias. Two of the studies (34,46) were very poorly reported in all of the six domains evaluated. Symmetric funnel plots showed a very small number of studies suffered from publication bias except for those studies included in the meta-analysis of skinrelated AEs ( Supplementary Figure 2: funnel plot).…”
Section: Risk Of Biasmentioning
confidence: 95%
See 1 more Smart Citation
“…Nearly 80% of the studies had low attrition and reporting bias. Two of the studies (34,46) were very poorly reported in all of the six domains evaluated. Symmetric funnel plots showed a very small number of studies suffered from publication bias except for those studies included in the meta-analysis of skinrelated AEs ( Supplementary Figure 2: funnel plot).…”
Section: Risk Of Biasmentioning
confidence: 95%
“…A high level of heterogeneity was observed in total AEs, GI-related and skin-related AEs among the included studies. For total AEs, a slight increase in heterogeneity (67% to 72%) and effect estimate (1.07 to 1.14) was observed when studies with a higher risk of bias (20,34,35,39,40,44,46,51,52,56) were excluded. Subgroup analysis by FQ agents did not change heterogeneity.…”
Section: Heterogeneitymentioning
confidence: 99%
“…In addition to the biological aspect of the low fosfomycin resistance rate, single-dose antibiotics are associated with a high degree of compliance and greater convenience, which may help prevent resistance from developing [19, 51, 52]. Maintenance of 100% adherence to optimized dosing regimens is critical for ensuring antimicrobial efficacy of the drug and prevention of resistance.…”
Section: Discussionmentioning
confidence: 99%
“…За час застосування в клінічній практиці проведено близько 60 контрольованих клінічних досліджень застосування пероральної форми фосфоміцину при гострому циститі, а також опубліковано результати метааналізів щодо цієї теми [3,7,13,16,17,19,21,22,. Вживання разової дози 3 г препарату порівнювали з хінолонами і фторхінолонами -норфлоксацином [27,32,33,36,37,42], ципрофлоксацином [41,52], офлоксацином [29], пефлоксацином [53], нітрофуранами [16,25,38,44,54], цефалоспоринами [39,55], амінопеніцилінами [28,48] і аміноглікозидами [26], а також триметопримом [31,43] та поєднанням сульфаметоксазолу/триметоприму (TMP/SMX) [29,30].…”
Section: ефективність фосфоміцину при інфекціях сечових шляхівunclassified